Down-regulation of brain-derived neurotrophic factor and its signaling components in the brain tissues of scrapie experimental animals. (October 2016) - Wang, Ting-Ting; Tian, Chan; Sun, Jing; Wang, Hui; Zhang, Bao-Yun; Chen, Cao; Wang, Jing; Xiao, Kang; Chen, Li-Na; Lv, Yan; Gao, Chen; Shi, Qi; et al.
Abstract: Prion is a unique nucleic acid-free pathogen that causes human and animal fatal neurodegenerative diseases. Brain-derived neurotrophic factor (BDNF) is a prototypic neurotrophin that helps to support the survival of existing neurons, and encourage the growth and differentiation of new neurons and synapses through axonal and dendritic sprouting. There are two distinct classes of glycosylated receptors, neurotrophin receptor p75 (p75NTR) and tropomyosin-related kinase (Trk), that can bind to BDNF. To obtain insights into the possible alterations of brain BDNF and its signaling pathway in prion disease, the levels of BDNF and several molecules in the BDNF pathway in the brain tissues of scrapie agents 263K-infected hamsters were separately evaluated. Western blots and/or immunohistochemical (IHC) assays revealed that BDNF, TrkB, GRB2 and p75NTR, were significantly downregulated in the brain tissues of scrapie-infected rodents at terminal stage. Double-stained immunofluorescent assay (IFA) demonstrated that BDNF and phospho-TrkB predominately expressed in neurons. Dynamic analyses of the brain samples collected at the different time-points during the incubation period illustrated continuous decreases of BDNF, TrkB, phospho-TrkB, GRB2 and p75NTR, which correlated well with neuron loss. However, these proteins remained almost unchanged in the prion infected cell line SMB-S15 compared with those of its normal cell line SMB-PS. These data suggest that the BDNF signaling pathway is severely hindered in the brains of prion disease, which may contribute, at least partially, to the neuron death.